MEMBANGUN DAMAI MELALUI MEDIASI: STUDI TERHADAP PEMIKIRAN HAMKA DALAM TAFSIR AL-AZHAR - Imam Taufiq (IAIN Ponorogo, 2014)
Scholars have formulated theories on conflict and designed its resolution on the basis of their expertise. They may come from various disciples and backgrounds, such as economics, law, sociology and even religion. In the context of Islamic religion, Muslim scholars use the verses of the Qur’an regarding conflict and extract their meanings through exegetical thematic method. This method offers explanation of conflict resolution from the Qur’anic perspectives concerning the verses on multiculturalism. But how are the multicultural verses understood? This article elaborates Hamka’s model of exegesis on multicultural verses in his work of Tafsir al-Azhar on conflict resolution. It shows that the Qur’anic verses not only have resolution principles but also give instructions on how to apply them. The terms used by the Qur’an include al-ta‘aruf, al-arham and al-taqwa. These concepts promote mediation that is applicable in various contexts of conflict such as in family, society, custom and law. Multiculturalism verses in Hamka’s model also offers phases of conflict resolutions, beginning from clarification to planning and mediation control. His offer, at least, stimulates Muslims’ awareness about Islamic unity and human unity.